Pengaruh Proactive Personality Terhadap Kepuasan Kerja Pegawai di Lembaga Pemasyarakatan Kelas IIB Klaten - Fatimah Rahman; Maki Zaenudin Subarkah (Jurnal Ilmiah Manajemen Kesatuan, 2022)
Job satisfaction is essential in the public service sector because satisfaction an employees are the key to providing high quality service, which very important in determining the success of the organization. Theoretically, proactive personality contributes to a higher job satisfaction over time through three essential features, which is that it’s self-initiative, is change-oriented, and a focus on the future. The purpose of this study was to know the impact of proactive personality on employee job satisfaction at the Class IIB Klaten Correctional Insttitution. This study uses quantitative research methods with a non-probability sample technique of 80 respondents. The data collection technique was carried out using a questionnaire distributed via google form. There are 47 statements that are used as indicators in this study. The data analysis technique was carried out through descriptive analysis tests, simple linear regression tests, significance tests and determination tests which were processed using IBM SPSS software version 22. The results showed that the independent variable, namely proactive personality, had a positive and significant influence on the dependent variable, namely job satisfaction. with the results of the t arithmetic significance test of 6.342 > t table 1.991. The results of the determination test were obtained with an R square value of 0.34 which indicates that the proactive personality variable has an influence of 34% on the job satisfaction variable, while the remaining 66% is influenced by other variables not described in this study. From the results of the study, it can be concluded that there is a positive and significant relationship between proactive personality and job satisfaction in the Class IIB Klaten Correctional Institution